Frontline Workers from Home: A Feminist Duoethnographic Inquiry of Mothering, Teaching, and Academia during the Initial Stages of the COVID-19 Pandemic - Almanssori, Salsabel; Hillier, Kimberly M. (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
In this article, we use a feminist lens to discuss and critique the unique challenges associated with our multidimensional identities as Ontario elementary schoolteachers, mothers, and academics. Employing a duoethnographic method, we recount our personal lived experiences of mothering, teaching, and academic related tasks during initial stages of the COVID-19 pandemic. We juxtapose our experiences at home, in our combined identities and roles, with the various levels of expectations set upon us. From the teaching front, these expectations include those from the government, school boards, and educational administration. On the academic front, there are the hidden expectations of writing and publishing, and being productive during mandated down time. At home, there are increases in domestic labour, caring for children and, for one of the authors, homeschooling. Taking into account the “Learn at Home” program, mandated synchronous learning, Ontario’s provincial approach to reopening schools for the 2020–2021 school year, and the literature on motherhood and academia, this article explores the nuanced experiences, barriers, and challenges that we encountered at the beginning and throes of the pandemic and into the unknown. The dialogic analysis of our experiences is rooted in feminist understandings of motherhood, teaching, and academia; it highlights the gendered issues of domestic and precarious labour, paid labour, caregiving, and mandatory social isolation.